Acacia karoo and its effects on the succession of dune forests in the Eastern Shores, Kwazulu-Natal - Maddams, C J (Department of Biological Sciences, 2017)
Acacia karoo arises following disturbance in the Dune Forests of Northern KwaZulu-Natal. Patches of A. karoo which had arisen as a result of the abandonment of fields by subsistence farmers in a dune forest matrix were studied. Previous authors have considered A. karoo to be part of a successional mechanism which leads towards a climax forest canopy (Mentis and Ellery, 1994; von Maltitz et al, 1996). This succession is questioned as a number of the conclusions of these authors were not verified by my own work. The present paradigm holds that the A. karoo is even aged and will senesce after 25 years, while recruitment does not occur in the patches. I find no evidence of canopy senescence and microhabitats within which recruitment of A. karoo occurred were identified. Further the introduction of other species in the patches is facilitated not through the A. karoo canopy but was shown to be facilitated by the presence of multi-stemmed canopy-trees of other species which had not been removed by the farmers. However, this introduction of other species into the patches was still limited, with certain species not found in even the very oldest patches (37 years old). No discernible chronosequence could be identified when comparing patches of different age, which casts doubt on the belief that these patches will eventually revert to climax dune forest.